Brain barriers virtual: an interim solution or future opportunity? - Hudson, Natalie (My University, 2022)
Background: Scientific conferences are vital communication events for scientists in academia, industry, and government agencies. In the brain barriers research field, several international conferences exist that allow researchers to present data, share knowledge, and discuss novel ideas and concepts. These meetings are critical platforms for researchers to connect and exchange breakthrough findings on a regular basis. Due to the worldwide COVID-19 pandemic, all in-person meetings were canceled in 2020. In response, we launched the Brain Barriers Virtual 2020 (BBV2020) seminar series, the first stand-in virtual event for the brain barriers field, to offer scientists a virtual platform to present their work. Here we report the aggregate attendance information on two in-person meetings compared with BBV2020 and comment on the utility of the virtual platform. Methods: The BBV2020 seminar series was hosted on a Zoom webinar platform and was free of cost for participants. Using registration- and Zoom-based data from the BBV2020 virtual seminar series and survey data collected from BBV2020 participants, we analyzed attendance trends, global reach, participation based on career stage, and engagement of BBV2020. We compared these data with those from two previous in-person conferences, a BBB meeting held in 2018 and CVB 2019. Results: We found that BBV2020 seminar participation steadily decreased over the course of the series. In contrast, live participation was consistently above 100 attendees and recording views were above 200 views per seminar. We also found that participants valued BBV2020 as a supplement during the COVID-19 pandemic in 2020. Based on one post-BBV2020 survey, the majority of participants indicated that they would prefer in-person meetings but would welcome a virtual component to future in-person meetings. Compared to in-person meetings, BBV2020 enabled participation from a broad range of career stages and was attended by scientists in academic, industry, and government agencies from a wide range of countries worldwide. Conclusions: Our findings suggest that a virtual event such as the BBV2020 seminar series provides easy access to science for researchers across all career stages around the globe. However, we recognize that limitations exist. Regardless, such a virtual event could be a valuable tool for the brain barriers community to reach and engage scientists worldwide to further grow the brain barriers research field in the future.
Keywords: brain barriers; BBV2020 seminar; virtual event; Education; COVID-19; Virtual seminar series; Brain barriers virtual; BBV2020; Blood–brain barrier